Pro-cyclicality and the Discretionary use of Loan Loss Provisions: Evidence from GCC Banks - Anandaraman, Adithya (2012)
Of the current debate on the resilience of banking systems, what seems to be one of the most critical issues is with regards to the inherent pro-cyclicality in banking systems all over the world particularly in its capital, credit extension and loan loss provisioning. The critical nature of this problem lies in the systemic risks it poses to the economy at large during economic downturns. This study examines the pro-cyclical nature of loan loss provisions in 65 banks from the oil-rich Gulf Co-operation Council region and also estimates whether these banks use discretion in loan loss provisions to manage their regulatory capital and income. Results establish that loan loss provisions are indeed pro-cyclical and backward looking. On the other hand, the study finds that banks do not use discretionary provisions to manage their capital. The study however does not find sufficient evidence whether banks smooth their incomes using provisions or not. The evidence of pro-cyclicality in provisioning amongst GCC banks established in this study is particularly important to regulators and banks in the GCC region to adopt more prudent provisioning practises that are forward-looking and counter-cyclical in order to curtail the systemic risk banks may pose otherwise on the economy.